Probiotic dairy products and consumption preferences in terms of sweetness sensitivity and the occurrence of childhood obesity - Kardas, Marek; Staśkiewicz, Wiktoria; Niewiadomska, Ewa; Kiciak, Agata; Bielaszka, Agnieszka; Fatyga, Edyta (Frontiers in Psychology, 2022)
Fermented dairy products such as yogurt contain many bioactive compounds. In addition, probiotic yogurts are an invaluable source of probiotic bacteria and are a group of probiotic products best accepted by children. There is plenty of research indicating an interdependence between yogurt consumption, body mass index, and adipose tissue percentage, which suggests that yogurt consumption may contribute to reducing the risk of becoming overweight or obese. In turn, the occurrence of overweight and obesity may be accompanied by a reduced sensitivity to sweetness, which modifies food preference selection and acceptance, including with yogurt. This study aimed to assess the preferences and consumption of yogurt in terms of sensitivity to recognize sweetness and obesity in a group of 7-9-year-old children. Body mass index and adipose tissue percentage obesity indicators were determined, and the frequency of fermented milk product consumption was assessed about the results of the sweetness recognition test as well as yogurt preferences. There was no significant relationship between body weight and the frequency of fermented milk product consumption. Correlations were found between the values of body mass index and the ability to recognize sweetness, which was significantly better recognized by underweight children or at normal body weight, moreover, those children with a higher ability to recognize sweetness significantly more frequently preferred plain unsweetened yogurt.